High Diversity of Novel Viruses in the Tree Pathogen Phytophthora castaneae Revealed by High-Throughput Sequencing of Total and Small RNA - Raco, Milica; Vainio, Eeva J.; Sutela, Suvi; Eichmeier, Aleš; Hakalová, Eliška; Jung, Thomas; Botella, Leticia (Frontiers in Microbiology, 2022)
Phytophthora castaneae, an oomycete pathogen causing root and trunk rot of different tree species in Asia, was shown to harbor a rich diversity of novel viruses from different families. Four P. castaneae isolates collected from Chamaecyparis hodginsii in a semi-natural montane forest site in Vietnam were investigated for viral presence by traditional and next-generation sequencing (NGS) techniques, i.e., double-stranded RNA (dsRNA) extraction and high-throughput sequencing (HTS) of small RNAs (sRNAs) and total RNA. Genome organization, sequence similarity, and phylogenetic analyses indicated that the viruses were related to members of the order Bunyavirales and families Endornaviridae, Megabirnaviridae, Narnaviridae, Totiviridae, and the proposed family “Fusagraviridae.” The study describes six novel viruses: Phytophthora castaneae RNA virus 1–5 (PcaRV1-5) and Phytophthora castaneae negative-stranded RNA virus 1 (PcaNSRV1). All six viruses were detected by sRNA sequencing, which demonstrates an active RNA interference (RNAi) system targeting viruses in P. castaneae. To our knowledge, this is the first report of viruses in P. castaneae and the whole Phytophthora major Clade 5, as well as of the activity of an RNAi mechanism targeting viral genomes among Clade 5 species. PcaRV1 is the first megabirnavirus described in oomycetes and the genus Phytophthora.